A study on domestic subcontractor in Kota Bharu : critical analysis of construction management in handling local project - Muhammad Shahmi , Mat Saat (2011)
Construction project involve- many parties namely- the contractor, consultants, clients, suppliers, subcontractor and so on. The main, contractor normally gives the works to the subcontractor to transfer the risks. The relationship between the main contractor and the subcontractor at times are problematic with the subcontractor at the mercy of the main contractor. This study is carried out to study the works generally carried out by the subcontractor and to analysis the- management also the financial of the subcontractor. The study is carried out in district Kota Bharu. This study is carried' out by interviews and questionnaires. The data are analyzed using statistical analysis and average index. From the study, the types of works carried out by the subcontractor are earthwork and piling works. The problems faced by the subcontractor are financial and late payment from the main contractor. The main factors that encourage the subcontractor to take the jobs are relationship network. The main sources of funding are payment from main contractor and' profit from previous job